An exploratory study examining educator perceptions about teaching and assessing entrepreneurship skills at Malaysian public higher education institutions - Meor Osman, Wan Sofiah; Girardi, A. (Journal of the World Universities Forum, 2012)
The development of soft skills has been the focus of new education and training practices globally and particularly within the Malaysian Higher Education System. Entrepreneurship skills in particular have been identified as one of seven soft skills in Malaysian Public Higher Education Institutions (HEIs). This present study examines what factors influence educator perceptions about teaching and assessing entrepreneurship skills. Specifically, the study looks at the amount of emphasis educators report placing on teaching and assessing entrepreneurship skills, and the factors which can impact this emphasis. The results from a quantitative cross-sectional study indicate that the university category; discipline area; employment level and status; years of teaching and industry experience; teaching qualifications; and gender have differential effects on educator perceptions about the emphasis placed on teaching and assessing of entrepreneurship skills. The implications of these outcomes will be discussed in line with recent higher education policy within this sector and the wider educational community.